Frizzled7 functions as a Wnt receptor in intestinal epithelial Lgr5+ stem cells - Flanagan, D.; Phesse, T.; Barker, N.; Schwab, R.; Amin, N.; Malaterre, J.; Stange, D.; Nowell, C.; Currie, S.; Saw, J.; Beuchert, E.; Ramsay, R.; et al. (Cell Press, 2015)
© 2015 The Authors. The mammalian adult small intestinal epithelium is a rapidly self-renewing tissue that is maintained by a pool of cycling stem cells intermingled with Paneth cells at the base of crypts. These crypt base stem cells exclusively express Lgr5 and require Wnt3 or, in its absence, Wnt2b. However, the Frizzled (Fzd) receptor that transmits these Wnt signals is unknown. We determined the expression profile of Fzd receptors in Lgr5+ stem cells, their immediate daughter cells, and Paneth cells. Here we show Fzd7 is enriched in Lgr5+ stem cells and binds Wnt3 and Wnt2b. Conditional deletion of the Fzd7 gene in adult intestinal epithelium leads to stem cell loss in vivo and organoid death in vitro. Crypts of conventional Fzd7 knockout mice show decreased basal Wnt signaling and impaired capacity to regenerate the epithelium following deleterious insult. These observations indicate that Fzd7 is required for robust Wnt-dependent processes in Lgr5+ intestinal stem cells.